STRATEGI KOMUNIKASI PERSUASIF DALAM MENARIK MINAT KREDITUR UNTUK MELAKUKAN KREDIT DI PT. ADIRA FINANCE PEKANBARU - Mita Lestari; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Human needs increasingly meningkatdan there is never a limit, while the increasingly difficult economic conditions, it forces everyone should have a strategy to meet kebutuhantersebut tersendidi. One of the strategies that today is the best solution to meet that need is to do credit. This action is not without reason, creditors increasingly interested in credit because it is easier to obtain goods to meet the needs. The number of companies that offer credit services, on condition that the easier and mild interest, help people easily meet their needs. One of the companies that provides credit services is Adira Finance.This research uses descriptive qualitative research methods conducted at PT. Adira Finance located on Jl. Sudirman, No. 21. Pekanbaru Riau with the selection of informants using Purposive Sampling technique. The object of this research is persuasive communication strategy of PT. Adira Finance Pekanbaru with research subject, creditor candidate, marketing operational chairman, marketing leader and sales marketing (kariyawan). Data collection techniques used were interviews, observation and documentation.The results obtained that the communication strategy of PT. Adira Finance Pekanbaru is done by using persuasive communication strategy by choosing the credibility of communicator of persuasive communication, persuasive message and media that is used. With the selection of communicators delivery of messages backed by education and can be trusted to run the activities provided by PT. Adira Finance Pekanbaru with maximum in attracting creditors to credit. In marketing, the message gained in introducing the product and doing credit in PT. Adira FInance Pekanbaru get the benefits of starting the process quickly, the condition is mudan and the interest is affordable in one day ready, free of fraud, this is because adira is a very trustworthy finance institution, and even been recognized by OJK. PT. Adira finance Pekanbaru using media such as sms, phone, social media (facebook, instagram, tweeter), brochures and baners to promote their products.Keywords: communication strategy, conducted